Unraveling the Uncharacterized Domain of Carocin S2: A Ribonuclease Pectobacterium carotovorum subsp. carotovorum Bacteriocin - Chung, Ping-Chen; Lagitnay, Ruchi Briam James S.; Derilo, Reymund C.; Wu, Jian-Li; Chuang, Yutin; Lin, Jia-De; Chuang, Duen-Yau (Microorganisms (Basel), 2022)
Carocin S2 is a bacteriocin with a low molecular weight generated by Pectobacterium carotovorum subsp. carotovorum 3F3 strain. The caroS2K gene, which is found in the genomic DNA alongside the caroS2I gene, which codes for an immunity protein, encodes this bacteriocin. We explored the residues responsible for Carocin S2’s cytotoxic or RNA-se activity using a structure-based mutagenesis approach. The minimal antibiotic functional region starts at Lys691 and ends at Arg783, according to mutational research. Two residues in the identified region, Phe760 and Ser762, however, are unable to demonstrate this activity, suggesting that these sites may interact with another domain. Small modifications in the secondary structure of mutant caroS2K were revealed by circular dichroism (CD) spectroscopy and intrinsic tryptophan fluorescence (ITF), showing ribosomal RNA cleavage in the active site. A co-immunoprecipitation test indicated that the immunity protein CaroS2I binds to CaroS2K’s C-terminus, while a region under the uncharacterized Domain III inhibits association of N-terminally truncated CaroS2K from interacting with CaroS2I. Carocin S2, a ribosomal ribonuclease bacteriocin, is the first to be identified with a domain III that encodes the cytotoxic residues as well as the binding sites between its immunity and killer proteins.